Dėl žodžių lie. abu, la. abi, pr. abbai gramatinio statuso - Rosinas, Albertas (Baltistica, 2000)
ON THE GRAMMATICAL STATUS OF LITH. abu, LATV. abi, OPR. abbai The article deals with the grammatical status of Lith. abu ‘both’, Latv. abi and OPr. abbai. In the Baltic literature, these words are traditionally referred to as numerals. However, the said words and the numerals – Lith. du ‘two’, Latv. divi, OPr. dwai – have different lexical meanings. The presupposition of the utterances with Lith. du, Latv. divi, OPr. dwai and Lith. abu, Latv. abi, OPr. abbai does not lead to the assumption that Lith. abu, Latv. abi and OPr. abbai are numerals. Cf. Jonas atsivežė du sūnus (‘John has brought two sons’) and Jonas atsivežė abu sūnus (‘John has brought both sons’). The first utterance implies that John may have even more sons (but he has brought only two), whereas the second utterance indicates that John does not have more sons (and he has brought all of them). The meaning of Lith. abu, Latv. abi, OPr. abbai suggests that the latter words should be considered pronouns. Moreover, these words function as pronouns in the structure of the text, too; the Lith. numeral du, Latv. divi, OPr. dwai usually occur in the focus, whereas the Lith. pronoun abu, Latv. abi, OPr. abbai occur in anaphoric structures. The contextual partners of the Lith. pronoun abu and the Latv. pronoun abi are always nouns which mean ‘forming a pair’ or ‘having two sides’: ãkys (‘eyes’), rañkos (‘hands’), aũsys (‘ears’), etc., (Latv. acis, rokas, ausis); kẽlias (‘road’), gãtvė (‘street’), tãkas (‘path’), geležìnkelis (‘railway’), ežià (‘boundary’), ùpė (‘river’), griovỹs (‘ditch’), kanãlas (‘canal’), pýlimas (‘dyke’), síena (‘wallֹ’), etc., (Latv. ceļš, iela, taka, dzelzceļš, eža, upe, grāvis, kanāls, dambis, valnis, robeža, siena). Lith. abu, abi and the Latv. dialect forms obu, obi are reflections of the pronominal dual inherited from Proto-Indo-European.